Mitochondrial Impairment May Increase Cellular NAD(P)H: Resazurin Oxidoreductase Activity, Perturbing the NAD(P)H-Based Viability Assays - Vasily A. Aleshin; Artem V. Artiukhov; Henry Oppermann; Alexey V. Kazantsev; Nikolay V. Lukashev; Victoria I. Bunik (Cells, 2015)
Cellular NAD(P)H-dependent oxidoreductase activity with artificial dyes (NAD(P)H-OR) is an indicator of viability, as the cellular redox state is important for biosynthesis and antioxidant defense. However, high NAD(P)H due to impaired mitochondrial oxidation, known as reductive stress, should increase NAD(P)H-OR yet perturb viability. To better understand this complex behavior, we assayed NAD(P)H-OR with resazurin (Alamar Blue) in glioblastoma cell lines U87 and T98G, treated with inhibitors of central metabolism, oxythiamin, and phosphonate analogs of 2-oxo acids. Targeting the thiamin diphosphate (ThDP)-dependent enzymes, the inhibitors are known to decrease the NAD(P)H production in the pentose phosphate shuttle and/or upon mitochondrial oxidation of 2-oxo acids. Nevertheless, the inhibitors elevated NAD(P)H-OR with resazurin in a time- and concentration-dependent manner, suggesting impaired NAD(P)H oxidation rather than increased viability. In particular, inhibition of the ThDP-dependent enzymes affects metabolism of malate, which mediates mitochondrial oxidation of cytosolic NAD(P)H. We showed that oxythiamin not only inhibited mitochondrial 2-oxo acid dehydrogenases, but also induced cell-specific changes in glutamate and malate dehydrogenases and/or malic enzyme. As a result, inhibition of the 2-oxo acid dehydrogenases compromises mitochondrial metabolism, with the dysregulated electron fluxes leading to increases in cellular NAD(P)H-OR. Perturbed mitochondrial oxidation of NAD(P)H may thus complicate the NAD(P)H-based viability assay.